Tourism Potential Resources Measurement: The Talaga Pancar Lake Case - Aceng Gima Sugiama; Femmy Indriany Dalimunthe; Rinjani Sastrowati (Politeknik Pariwisata Makassar, Indonesia, 2022)
This paper is aimed to measure the potential resources of tourism based on the criteria of tourist attraction, accessibility, infrastructure and facilities, and environmental degradation. The research using a case study in Talaga Pancar Lake based on qualitative and quantitative data with a descriptive explanation. Data through depth interviews were obtained from the manager and operator, while observed and measuring the potential tourism resource by using a rating scale. Results showed that tourist attractions were a medium category, that's the existing natural tourist attractions were sufficient to be used as potential as natural tourist attractions. The available accessibility was a potential medium, that the place has sufficient infrastructure and superstructure for tourists to reach the place. The level of environmental degradation was medium, that the impact of damage to environmental assets conditions was insufficiently maintained. Infrastructure assets were a high category, which means that the availability of assets is much complete. While the availability of supporting facilities was not sufficient by the adequacy standard for tourism destination services.